Chromosome synapsis and recombination in simple and complex chromosomal heterozygotes of tuco-tuco (Ctenomys talarum: Rodentia: Ctenomyidae) - Basheva, Ekaterina A. (2014)
The chromosomal speciation hypothesis suggests that irregularities in synapsis, recombination, and segregation in heterozygotes for chromosome rearrangements may restrict gene flow between karyotypically distinct populations and promote speciation. Ctenomys talarum is a South American subterranean rodent inhabiting the coastal regions of Argentina, whose populations polymorphic for Robertsonian and tandem translocations seem to have a very restricted gene flow. To test if chromosomal differences are involved in isolation among its populations, we examined chromosome pairing, recombination, and meiotic silencing of unsynapsed chromatin in male meiosis of simple and complex translocation heterozygotes using immunolocalization of the MLH1 marking mature recombination nodules and phosphorylated histone γH2A.X marking unrepaired double-strand breaks. We observed small asynaptic areas labeled by γH2A.X in pericentromeric regions of the chromosomes involved in the trivalents and quadrivalents. We also observed a decrease of recombination frequency and a distalization of the crossover distribution in the heterozygotes and metacentric homozygotes compared to acrocentric homozygotes. We suggest that the asynapsis of the pericentromeric regions are unlikely to induce germ cell death and decrease fertility of the heterozygotes; however, suppressed recombination in pericentromeric areas of the multivalents may reduce gene flow between chromosomally different populations of the Talas tuco-tuco.